The Dynamic Mathematics Software for Teaching Variance - Li Li; Haiming Tang (Edumatika : Jurnal Riset Pendidikan Matematika, 2020)
Abstract. In traditional teaching, many teachers often ignore the process of students' knowledge exploration, devote themselves to instilling knowledge to students in a short time, and then adopt the sea of questions tactics. Such teaching is only limited to the stage of telling students what "variance" is and how to use it, and ignores the birth process and meaning of "variance". The purpose of this research is to see the differences in classes that use dynamic mathematics software and traditional classes. The method in this research is descriptive qualitative. The sample in this study was seventh-grade students at one of the junior high schools in China. The content of this research design is the use of dynamic mathematics technology, focusing on the understanding of the concept of efficiency-improving variance, and the form innovation of the course design is design and record before and after optimization-evaluation and analysis before and after optimization. This article mainly takes the concept of teaching variance topic as an example to try to explore the teaching design of optimizing the important and difficult points of mathematics. This study shows that Hawgent dynamic mathematics software makes students get deep learning and makes teaching and learning activities more active. Then the teacher can continue to use Hawgent dynamic mathematics software to make students more active. Abstrak. Dalam pengajaran tradisional, banyak guru sering mengabaikan proses eksplorasi pengetahuan siswa, fokus menanamkan pengetahuan kepada siswa dalam waktu singkat, dan kemudian memberi banyak soal untuk diselesaikan. Pengajaran semacam itu hanya sebatas tahap memberi tahu siswa apa itu "varians" dan bagaimana menggunakannya, serta mengabaikan proses penemuan konsep dan makna "varians". Tujuan dari penelitian ini adalah untuk melihat perbedaan kelas yang menggunakan dynamic mathematics software dan kelas tradisional. Metode dalam penelitian ini adalah deskriptif kualitatif. Sampel dalam penelitian ini adalah siswa kelas tujuh di salah satu sekolah menengah pertama di China. Desain penelitian ini adalah pemanfaatan teknologi dynamic mathematics software, menitikberatkan pada pemahaman konsep varians, dan inovasi bentuk rancangan penelitian rekam sebelum dan sesudah optimalisasi-evaluasi dan analisis sebelum dan sesudah optimasi. Artikel ini terutama mengambil konsep pengajaran pada bahasan varians sebagai contoh untuk mencoba mengeksplorasi desain pengajaran dalam mengoptimalkan poin-poin matematika yang penting dan sulit. Penelitian ini menunjukkan bahwa dynamic mathematics software Hawgent membuat siswa mendapatkan pembelajaran yang mendalam dan membuat kegiatan belajar mengajar menjadi lebih aktif. Oleh karena itu, guru dapat menggunakan dynamic mathematics software Hawgent untuk membuat siswa lebih aktif.